Early Physiotherapy Rehabilitation of Congenital Scoliosis Aftercorrective Surgery- A Case Report - Desai, Prapti R.; Ramdurgkar, Rama; Dalvi, Sairani R; Patil, Vaibhav N (Journal of Neonatal Surgery, 2025)
A 15-year-old schoolgirl presented with right shoulder elevation and restricted neck mobility on the same side, which had been noted prior to her referral. Radiological and physical assessments revealed an S-shaped scoliotic curvature located in the proximal dorsal region. The patient subsequently underwent surgical correction of the spinal deformity. Postoperative rehabilitation played a critical role in optimizing therapeutic outcomes. An early, structured rehabilitation protocol was introduced, focusing on targeted exercises aimed at accelerating recovery, fostering functional independence, and enhancing the long-term quality of life in post-surgical scoliosis patients.Early intervention in rehabilitation is increasingly recognized as a cornerstone of effective scoliosis management post-surgery. It not only aids in preventing secondary complications but also contributes significantly to the patient’s physical and psychological well-being. A multidisciplinary approach, involving physiotherapists and orthopaedic specialists further enhances the overall success of post-surgical recovery